Maxillary Anterior Implant Placement with Autogenous Guided Bone Regeneration - Pratibha Chaudhary; Pravesh Mehra (Indian Journal of Medical Specialities)
Anterior implant placement is quite a challenge that clinicians face due to ridge deformity as it is an esthetic zone. This case report presents an innovative approach of using autogenous bone graft (ABG) to correct an atrophic ridge in conjunction with implant placement. A 23-year-old male patient lost a maxillary central incisor tooth due to trauma followed by abscess formation. Due to severe and active infection, ridge augmentation was not feasible at the time of tooth extraction, resulting in prominent loss of buccal plate. The guided bone regeneration was performed at the extracted site procuring graft from the parasymphysis region, followed by the implant placement. After 1 year of function, both clinical and radiographic examinations revealed promising and stable treatment outcomes. ABG from the parasymphysis region is a good option for ridge augmentation procedures. The only disadvantage is the second operating site.